PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS PENEMUAN TERBIMBING PADA MATERI STATISTIKA UNTUK SISWA KELAS XI IPA SMA - Almira, Vivien; Zulfaneti, Zulfaneti; Yunita, Alfi (Pendidikan Matematika, 2014)
ABSTRACKTeaching materials represent one of the matter that able to influence the quality of learning. Teaching materials should facilitate students to discover concepts independently, so that the mindset of students thrive. At this research, is developed a teaching materials in the form of sheet activity of student (LKS) based on guided discovery. Research type is development research by using model 4-D which consist of 4 phase that is: define, design, develop, and disseminate. Result of validation indicate that sheet activity of student (LKS) based on guided discovery have validity 3,77 which including at criterion very valid which is evaluated from didactic requirements, construction requirements, and technical requirements.